Integrated Impacts of Urban Spatial Form on Thermal Environment and Zonal Regulation under the Perspective of Spatial Heterogeneity - Yan Jinlong; Yin Chaohui; An Zihao; Zhang Simin; Wen Qian; Chen Weiqiang (Redai dili)
Analyzing the spatial relationship between urban spatial patterns and the thermal environment and quantifying zoning to regulate the urban thermal environment according to local conditions is essential. Previous research on the spatial heterogeneity of factors influencing thermal environments is lacking, and there are shortcomings in the actionability of thermal environment regulation. This study takes the main urban area of Wuhan as an example, based on multi-source spatial data such as Landsat-8 remote sensing images, urban land classification, and buildings, integrates geodetectors and a geographically weighted regression model (MGWR) to investigate the mechanism of the influence of the urban form on the thermal environment under the control unit at the global and local levels, and finally utilizes the K-mean clustering approach to perform impact zoning. First, the high-temperature areas in the main urban area of Wuhan are mainly located in the core area of the old city of Hankou and the Wuchang District, which are located on both sides of the Yangtze River, as well as in the industrial zones northeast and southwest of the city. In terms of land-use types, industrial, logistics and warehousing, and street and transportation had higher average surface temperatures, whereas water area, green space and square, and agricultural and forestry had lower average surface temperatures. Second, the three-dimensional (3D) building indicator had a greater overall impact on the thermal environment than the two-dimensional (2D) urban land-use type indicator. Building density (q = 0.479) was the dominant factor affecting the thermal environment. While the share of water area in 2D form had the strongest explanatory power, the other indicators were relatively weaker. Third, there was spatial heterogeneity in the impact of indicators on the thermal environment, with strong locally driven characteristics for indicators such as vegetation cover, percentage of industrial land area, and building density (BD). Finally, according to the MGWR regression coefficients of each indicator, the main urban area of Wuhan was divided into four types of impact zones, and the intensity and direction of the impact of indicators in different impact zones changed, which confirms the necessity of a zoning policy. 3D buildings form the dominant zone and the BD strong dominant zone are suggested to adjust the urban building form as the main goal, the percentage of water area and BD co-dominant zones are suggested to optimize the urban blue-green space as the main regulation goal to improve its cooling efficiency, and the integrated transition zone is suggested to synergistically optimize the 2D/3D urban spatial form. In conclusion, from the perspective of planning practice, combined with the different impact characteristics of each control area, we propose a differentiated control strategy combining "planning units + planning indicators," which provides a practical approach to optimize the climate-friendly urban form.